WEBINAR TALENT SCOUTING BOLA VOLI BAGI PELATIH KLUB BOLA VOLI - Bambang Sutiyono (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract The development of gadget technology among the community makes the younger generation have a tendency to be lazy about their activities. The physical development and mobility of children are difficult to monitor, so that it becomes a challenge for coaches and coaches to find children who have talents and potential to be nurtured. Through this activity, it is hoped that the trainers will get provisions and knowledge in order to monitor and look for talents from children who have the potential to be nurtured. The conditions of the Covid-19 Pandemic that have been going on so far, forcing various activities outside the home and involving many people are difficult to carry out. Sports activities are also recommended to do activities independently and not in groups. For volleyball, especially among students, this condition is increasingly becoming an obstacle that cannot be avoided. Various forms of play on the field become difficult to use as a means of volleyball activity. Training activities aimed at providing insight, knowledge and competence on monitoring the talents and potential of volleyball players are carried out using online media through webinars. The resulting output is an additional understanding and insight into talent scouting for prospective volleyball athletes which is a provision for coaches and coaches in recruiting talented volleyball athletes. The impact resulting from this activity is that it is hoped that the seeds of talented volleyball athletes can be obtained in order to increase the funds of prospective volleyball athletes who are able to perform optimally. Abstrak Perkembangan teknologi gadget dikalangan masyarakat menjadikan generasi muda memiliki kencenderungan untuk malas berkatifitas. Perkembangan fisik dan kemampuan gerak anak menjadi hal yang sulit untuk dipantau, sehingga menjadi tantangan tersendiri bagi pelatih dan pembina dalam mendapatkan anak yang memiliki bakat dan potensi untuk dibina. Melalui kegiatan ini diharapkan para pelatih mendapatkan bekal dan pengetahuan dalam rangka memantau dan mencari bakat dari anak yang berpotensi untuk dibina. Kondisi Pandemi Covid-19 yang berlangsung selama ini, memaksa berbagai kegiatan di luar rumah dan melibatkan banyak orang menjadi hal yang sulit dilaksanakan. Kegiatan olahraga juga disarankan lebih kepada melakukan aktivitas secara mandiri dan tidak berkelompok. Untuk cabang bola voli terutama dikalangan pelajar, kondisi in semakin menjadi kendala yang tidak bisa dihindari. Berbagai bentuk permainan di lapangan menjadi sulit untuk dijadikan sarana beraktivitas permainan bola voli. Kegiatan pelatihan yang bertujuan memberikan wawasan, pengetahuan dan kompetensi tentang pemantauan bakat dan potensi pemain bola voli dilakukan dengan media online melalui kegiatan webinar. Luaran dihasilkan adalah tambahan pemahaman dan wawasan tentang pemanduan bakat bagi calon atlet bola voli yang merupakan bekal bagi pelatih dan pembina dalam merekrut calon atlet bola voli berbakat. Dampak yang dihasilkan dari kegiatan ini adalah diharapakan dapat diperoleh bibit atlet bola voli berbakat guna menambah pundi calon atlet bola voli yang mampu berprestasi secara optimal.